Updates on Valvular Heart Disease - Borer, Jeffrey S. Palacios, Igor F. O'Gara, Patrick Connolly, Heidi Rajamannan, Nalini (MD Conference Express, 2005)
Aortic regurgitation (AR) suffers from sparse data, according to Jeffrey S. Boyer, MD, of the Weill Medical College of Cornell University in New York, NY. “AR has been studied less than any other form of valvular heart disease,” he said.